Empowering Huruk Gabe Aeksorseang Musical Studio as Bataknese Musical Instrument Craftman in Lintongnihuta Village, Samosir - Sembiring, Bebas; Purba, Mauly; Adha, Ishbir Mujahid (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Huta Gabe Aeksorseang studio is a traditional art studio that helped preserve traditional culture, especially the Batak Toba. The presence of this art studio has stimulated creative economy activities within the region. The problems currently being faced by the Huta Gabe Aeksorseang studio have not been made optimal yet. Products that had been sold nationally but had not well known to many other Indonesian consumers due to there is no product brand. The daily activities of this art gallery cultivate traditional music. This community services is carried out with a focus on solving partner problems by providing appropriate science and technology for the local community, especially for the management of the Studio. The method of making traditional musical instruments is still not optimal so that the resulting sound quality is not correctly produced. Science and technology has been given to partners related to production and marketing techniques that have been carried out. We also provided online marketing strategies to assist the online marketing activities of the Huta Gabe Aeksorseang studio. Technical equipment is also provided to help partners improve product quality and product competitiveness with lower production costs. Heavy equipment such as welding machines in the area makes production costs high. With the help of the equipment provided, partners will be more efficient in production, thereby increasing partner competitiveness.